Implementation of Mobile-Based Management Information Systems to Increase Employee Productivity - Nova Elsyani Nova; Muhammd Irwan Padli Nasution (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to analyze how the implementation of a mobile-based management information system (MIS) can improve employee productivity in organizations. The rapid development of information technology encourages organizations to adapt to work systems that are more flexible, efficient, and responsive to operational needs. Mobile-based MIS enables real-time data access, faster communication between employees, and a more efficient reporting process compared to conventional methods. This study uses a qualitative descriptive approach with a case study of a service company in Indonesia that has implemented a mobile-based MIS for more than a year. The results show that this system not only facilitates coordination between units but also supports faster and more accurate decision-making, thereby improving employee performance. In addition, mobile-based MIS helps organizations optimize workflows, reduce human error, and improve overall operational effectiveness. These findings confirm that the use of mobile-based information technology has a positive contribution to organizational productivity and success in the digital era.